2011
DOI: 10.1016/j.measurement.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Development of microcontroller based thermogravimetric analyzer

Abstract: a b s t r a c tThermogravimetric analyzer (TGA) is an analytical technique extensively used to study the thermal decomposition of inorganic solids, their kinetics, reaction mechanisms, chemical property, structure of intermediate and final products and synthetic conditions. This paper reports the development of microcontroller based thermogravimetric analyzer. The TGA has been setup with additional features like controlled gas delivery system suitable for the study of decomposition (gas-solid interaction) in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The oven was designed to operate with a power supply of 120 V (AC) at 60 Hz. Electrical current/voltage measurements showed that the mean power demanded by the electrical resistance (cartridge heater) was 60 W. The control system uses a microcontroller implemented on a specially designed electronic board, similar to the control system used in other devices reported in the literature (Affanni, 2013;Ahlers & Ammermuller, 2013;Devaraju et al, 2011;Oliveira, Freire, Deep, & Barros,1998). A schematic of the electronic components and the interconnections of the control system are shown in Figure 2.…”
Section: Electric and Control Systemmentioning
confidence: 99%
“…The oven was designed to operate with a power supply of 120 V (AC) at 60 Hz. Electrical current/voltage measurements showed that the mean power demanded by the electrical resistance (cartridge heater) was 60 W. The control system uses a microcontroller implemented on a specially designed electronic board, similar to the control system used in other devices reported in the literature (Affanni, 2013;Ahlers & Ammermuller, 2013;Devaraju et al, 2011;Oliveira, Freire, Deep, & Barros,1998). A schematic of the electronic components and the interconnections of the control system are shown in Figure 2.…”
Section: Electric and Control Systemmentioning
confidence: 99%
“…In order to improve the research on thermogravimetric technique, scholars and research institutes in related fields from China, the United States, Russia, France, Germany, Netherlands, Norway, India, Japan, and Serbia have made great efforts in the research on various specimen specifications and purposes [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Most of the studies are intended to increase temperature range, specimen weight range, heating rate, temperature accuracy, and weighing accuracy of thermogravimetric systems.…”
Section: Introductionmentioning
confidence: 99%